P219 THE ROLE OF PET-CT IN THE EVALUATION OF LYMPH NODE INVOLVEMENT IN ESOPHAGEAL AND GASTROESOPHAGEAL JUNCTION CARCINOMA - A 5-YEAR SINGLE CENTER EXPERIENCE. (23rd November 2019) - Vergadis, Chrysovalantis; Mpaili, Eustratia; Syllaios, Athanasios; Mpoura, Maria; Michalinos, Adamantios; Karavokyros, Ioannis; Alexandrou, Andreas; Charalabopoulos, Alexandros; Schizas, Dimitrios; Liakakos, Theodore
Abstract: Aim: To determine the efficacy of positron emission tomography-computed tomography (PET-CT) in the evaluation of lymph node status during preoperative staging on patients with esophageal and gastrοesophageal junction carcinoma compared to the final histopathological findings. Background & Methods: Data on patients that underwent esophagectomy from 01/03/2014 to 01/03/2019 were prospectively collected and retrospectively reviewed. Based on the medical records, the following parameters were extracted and analyzed: patient demographics, histopathological parameters, surgical and oncological outcomes. All patients were staged according to the AJCC 8th edition. Results: A total of 79 patients underwent Ivor Lewis or McKeown esophagectomy for either squamous cell carcinoma (n= 7 patients) or adenocarcinoma of esophagus or gastroesophageal junction (n= 72 patients). In 60 cases, clinical staging was conducted without performing PET- CT, while 19 cases underwent PET-CT. Among the 19 patients, 16 (84.2%) were men, and 3 (15.8 %) were women. Mean age was 62 years, (range 41- 72). Mean nodal harvest per patient was 30.6 lymph nodes. Twelve out of 19 patients (63.2%) revealed lymph node invasion, with a mean of 5.6 positive lymph nodes per patient. PET-CT identified the primary tumor in all 19 patients (100%). PET-CT demonstrated 100% compliance with the final histopathological reports regarding N status in only 5 out of 19 cases (26.3%). Four patients were staged as N0 both pre- and postoperatively, while one was deemed positive by PET-CT in right paracardial lymph nodes which was histopathologically confirmed. In other 4 patients (21.1%), PET-CT was 100% false negative, whereas in 3 patients (15.8%) PET-CT was 100% false positive. In the remaining 7 patients, PET-CT findings were in accordance with the pathology report in 7 out of 25 examined lymph node stations, false positive in 9 out of 25 and false negative in 9 out of 25. Conclusion: PET-CT seems to have a considerable number of false positive and false negative results in esophageal cancer in our study as far as N-staging is concerned. Further studies with larger sample size are needed to reach more conclusive results.